North American legends - Haviland, Virginia; Strugnell, Ann. (New York : Collins, 1979)
Presents tall tales indigenous to America, tales of European and African immigrants, and folklore of American Indians and Eskimos.
Includes bibliographical references.
Keywords: Tales -- United States; Indians of North America -- Folklore; Folklore -- United States; Indians of North America -- Folklore